Presence of cimicid bugs (Hemiptera: Cimicidae) on a crowned eagle (Harpyhaliaetus coronatus) nestling - Santillan, Miguel Angel (2009)
Fil: Santillan, Miguel Angel. Universidad Nacional de La Pampa; Argentina